SISTEM INFORMASI GEOGRAFIS PEMBANGUNAN JARINGAN IRIGASI DI PROVINSI BENGKULU BERBASIS WEBSITE MENGGUNAKAN GOOGLE MAP - Ernawati Ernawati; Liza Yulianti; Eko Suryana (Jurnal Media Infotama, 2014)
Has conducted research on the development of geographic information systems in the province of Bengkulu irrigation network-based website using google map on public works ministry Bengkulu. This study aims to provide information about how to create a geographic information system of irrigation network construction based on public works ministry websites by using google map. Data were collected on March 25, 2014 in the form of project data that has been finished by the contractor. The data is then processed into a source of discussion in this study. Besides the most important data is the location coordinates of the coordinate construction of irrigation networks because this is what it used to indicate the location or position of the project has been done. The results of this study indicate that the need for a geographic infor-mation system to be able to submit an information to the public.Keyword: Geograpich Information System, irrigation network, Google Map